Oxygen absorbing material and method for storing articles

By using adjacent structures of the substrate, inorganic layer and epoxy resin cured material layer in the oxygen absorbing material, the problem of oxidation deterioration in high humidity environment is solved, and efficient preservation of aqueous items is achieved.

CN119156286APending Publication Date: 2024-12-17MITSUBISHI GAS CHEM CO INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380038634.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-11
Filing Date
2023-04-28
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

It is difficult for the existing oxygen absorbers to effectively store aqueous articles in high humidity environments, and there is a problem of oxidation deterioration.

Method used

An oxygen absorbing material composed of a substrate, an inorganic layer and an epoxy resin cured product layer is used to achieve oxygen absorbability through the adjacent structure of the inorganic layer and the cured product layer, which is suitable for storage of items in high humidity environments.

Benefits of technology

It provides oxygen absorbing materials particularly suitable for aqueous articles and high humidity environments, effectively inhibiting oxidation and deterioration of articles and improving preservation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005119450460000071
    Figure BDA0005119450460000071
  • Figure BDA0005119450460000101
    Figure BDA0005119450460000101
  • Figure BDA0005119450460000221
    Figure BDA0005119450460000221
Patent Text Reader

Abstract

[1] An oxygen absorbing material having a base material (I), an inorganic layer (II), and a cured product layer (III) of an epoxy resin composition containing an epoxy resin and an epoxy resin curing agent, the epoxy resin curing agent including an amine-based curing agent, the inorganic layer (II) being adjacent to the cured product layer (III), [2] a method for storing an article, the method includes any one or more of the following methods: (1) housing the article in a packaging material in which the oxygen-absorbing material described in [1] is sealed; or (2) the article is housed in a packaging material that has [1] the oxygen-absorbing material in at least a portion thereof, and the oxygen permeability of the packaging material is 1 cc / (m < 2 > day atm) or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an oxygen absorbing material and a method for preserving articles. Background Art

[0002] As one of the preservation technologies for food, medicine, etc., there is a known preservation technology using an oxygen absorber. Specifically, the oxygen absorber is placed inside a sealed package together with the preservation object, and the inside of the sealed package is made oxygen-free, thereby suppressing oxidative degradation, discoloration, etc. of the preservation object.

[0003] As the above oxygen absorber, those formed by inorganic materials and those formed by organic materials are proposed. As the inorganic material, materials using metal powders such as iron, sulfites, bisulfites, and dithionites can be listed, and as the organic material, materials using L-ascorbic acid, isoascorbic acid and their salts, sugars such as glucose, and reducing polyols such as catechol and pyrogallol can be listed.

[0004] Oxygen-absorbing resin compositions containing improved oxygen absorbers are also known. For example, Patent Document 1 discloses an oxygen-absorbing resin composition having oxygen-absorbing ability even in an atmosphere without or with little moisture, the composition comprising a metal obtained by subjecting an alloy containing at least one transition metal selected from the group consisting of iron, cobalt, nickel, and copper and aluminum to an aqueous alkali solution, an oxygen absorber having a specific surface area measured by a BET method of a predetermined value or more, and a thermoplastic resin, and having a moisture content of a predetermined value or less.

[0005] In addition, a technique for improving the packaging material in the oxygen absorber attached to the inner surface of the center seal side of the packaging bag when pillow packaging is performed on food has also been studied. For example, Patent Document 2 discloses an oxygen absorber that is not easy to fall off or damage the food during the packaging process and has an excellent food preservation effect. The oxygen absorber is formed by sealing an oxygen absorbing composition containing iron powder or a reducing organic compound, an alkaline compound and water in a packaging bag formed by heat-pressing the peripheral portion of a sheet formed by stacking prescribed packaging materials, and the stiffness value of the heat-sealed portion formed by heat bonding at the peripheral portion of the packaging bag is within a prescribed range.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2015-7148

[0009] Patent Document 2: Japanese Patent Application Publication No. 2016-140810 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] The oxygen absorbers used in Patent Documents 1 and 2 both contain metal powders such as iron powder or reducing organic compounds. On the other hand, an oxygen absorber material is being studied that uses a novel material as an oxygen absorber and can be easily made into a film form even without mixing the oxygen absorber into a film, and is suitable for the storage of water-containing articles or the storage of articles in a high humidity environment.

[0012] An object of the present invention is to provide an oxygen absorber suitable for storing water-containing articles or storing articles in a high-humidity environment, and a method for storing articles using the oxygen absorber.

[0013] Solutions for solving problems

[0014] The present inventors have found that the above-mentioned problems can be solved by forming an oxygen absorber having a specific structure including a substrate, an inorganic layer, and a cured product layer of a predetermined epoxy resin composition.

[0015] That is, the present invention relates to the following contents.

[0016] [1] An oxygen absorbing material comprising: a substrate (I), an inorganic layer (II), and a cured layer (III) of an epoxy resin composition containing an epoxy resin and an epoxy resin curing agent, wherein the epoxy resin curing agent includes an amine curing agent, and the inorganic layer (II) is adjacent to the cured layer (III).

[0017] [2] A method for storing an article, using the oxygen absorbing material described in [1], the method comprising any one or more of the following (1) or (2),

[0018] (1) placing the aforementioned article in a packaging material enclosing the oxygen absorbing material;

[0019] (2) The article is placed in a packaging material, wherein at least a portion of the packaging material has the oxygen absorbing material, and the oxygen permeability of the packaging material is 1 cc / (m 2 ·day·atm) or less.

[0020] [3] Application of a laminate as an oxygen absorbing material, the laminate comprising: a substrate (I), an inorganic layer (II), and a cured layer (III) of an epoxy resin composition containing an epoxy resin and an epoxy resin curing agent, wherein the epoxy resin curing agent includes an amine curing agent, and the inorganic layer (II) is adjacent to the cured layer (III).

[0021] Effects of the Invention

[0022] According to the present invention, it is possible to provide an oxygen absorbent material which is particularly suitable for the storage of water-containing articles or the storage of articles under a high-humidity environment, and a method for storing articles using the oxygen absorbent material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 In the figure, (a) is a photograph of the appearance of the rice cake (kiri mochi) before storage used in Example 24, Comparative Example 2 and Comparative Example 3. (b) is a photograph of the appearance of the rice cake in Example 24, (c) is a photograph of Comparative Example 2, and (d) is a photograph of the appearance of the rice cake after the rice cake was stored in a bag-shaped packaging material in Comparative Example 3 and the packaging material was stored at 40° C. and a relative humidity of 90% for 2 months.

[0024] Figure 2 In the figures, (a) is a photograph of the appearance of the cheese cod before storage used in Example 25, Comparative Example 4 and Comparative Example 5. (b) is a photograph of the appearance of the cheese cod after the cheese cod was placed in a bag-shaped packaging material in Example 25, (c) is a photograph of the appearance of the cheese cod after the packaging material was stored in an environment of 40° C. and a relative humidity of 90% for 2 months in Comparative Example 5. DETAILED DESCRIPTION

[0025] [Oxygen Absorber]

[0026] The oxygen absorber of the present invention comprises: a substrate (I), an inorganic layer (II), and a cured layer (III) of an epoxy resin composition containing an epoxy resin and an epoxy resin curing agent, wherein the epoxy resin curing agent includes an amine curing agent; the inorganic layer (II) is adjacent to the cured layer (III). The oxygen absorber of the present invention has oxygen absorption and is particularly suitable for the storage of water-containing articles.

[0027] The reason why the oxygen absorber of the present invention exhibits the above-mentioned effect is not clear, but is considered as follows.

[0028] It is believed that the cured layer (III) of the epoxy resin composition of the oxygen absorber of the present invention is oxidized by contact with the inorganic layer (II), thereby exhibiting oxygen absorbency. It is also believed that the inorganic layer (II) is also oxidized due to the influence of the adjacent cured layer (III). Furthermore, the inorganic layer (II) and the cured layer (III) have not only oxygen absorbency but also gas barrier properties, so the packaging material using the oxygen absorber of the present invention is suitable for the storage of articles that are easily oxidatively degraded.

[0029] In particular, the present inventors have found that the oxygen absorbency of the cured layer (III) caused by contact with the inorganic layer (II) is exhibited by water as a trigger. Therefore, the oxygen absorber of the present invention is suitable for the storage of water-containing articles or articles in a high humidity environment.

[0030] The layer structure of the oxygen absorbing material of the present invention is not particularly limited if it has at least one layer of substrate (I), inorganic layer (II) and cured layer (III). However, from the perspective of showing oxygen absorption performance, it is necessary that the inorganic layer (II) is adjacent to the cured layer (III). From the perspective of showing oxygen absorption performance and protecting the inorganic layer (II), the layer structure of the oxygen absorbing material is preferably a structure having a substrate (I), an inorganic layer (II) and a cured layer (III) in sequence, and the inorganic layer (II) is adjacent to the cured layer (III).

[0031] In addition, from the viewpoint of improving the strength of the oxygen absorber, the oxygen absorber preferably has two or more substrates (I), and more preferably has a substrate (IA), the inorganic layer (II), the cured layer (III), and a substrate (IB) in this order.

[0032] <Base Material (I)>

[0033] From the viewpoint of improving oxygen absorbency and flex resistance, the substrate (I) used in the oxygen absorber of the present invention is preferably a plastic film.

[0034] Examples of the plastic film used as the substrate (I) include polyolefin films such as low-density polyethylene, high-density polyethylene, linear low-density polyethylene, and polypropylene; polyester films such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate; polyamide films such as nylon 6, nylon 6,6, and poly(m-phenylene adipamide) (N-MXD6); polyimide films; biodegradable films such as polylactic acid films; polyacrylonitrile films; poly(meth)acrylic acid films; polystyrene films; polycarbonate films; ethylene-vinyl acetate copolymer saponified (EVOH) films, polyvinyl alcohol films, and the like.

[0035] Among the above, from the viewpoints of oxygen absorbency, bending resistance, strength and heat resistance, the substrate (I) is preferably a film selected from the group consisting of polyolefin films, polyester films, polyamide films and polyimide films, more preferably a film selected from the group consisting of polyolefin films and polyester films, and further preferably a polypropylene film or a polyethylene terephthalate (PET) film.

[0036] The film may be an unstretched film or a film stretched in a uniaxial or biaxial direction.

[0037] When the oxygen absorber has a substrate (IA) and a substrate (IB), the substrate (IA) and the substrate (IB) may be formed from the same resin or may be formed from different types of resins. From the viewpoint of ease of recycling, the substrate (IA) and the substrate (IB) are preferably formed from the same resin, and the substrate (IA) and the substrate (IB) are more preferably polypropylene films.

[0038] The thickness of the substrate (I) can be appropriately selected according to the application and is not particularly limited, but is preferably 5 to 300 μm, more preferably 5 to 100 μm, and even more preferably 10 to 60 μm from the viewpoint of gas barrier properties and strength. The above thickness is the thickness per substrate (I).

[0039] <Inorganic Layer (II)>

[0040] The inorganic layer (II) used in the oxygen absorber of the present invention may be composed of a metal foil or formed by a vapor deposition method. From the viewpoint of improving oxygen absorbency, the inorganic layer (II) is preferably an inorganic vapor-deposited layer formed by a vapor deposition method.

[0041] The inorganic substance constituting the inorganic layer (II) is preferably an inorganic substance that can form an inorganic vapor-deposited layer, for example, silicon, aluminum, magnesium, calcium, zinc, tin, nickel, titanium, zirconium, carbon or their oxides, carbides, nitrides, oxynitrides, etc., and one or more of them can be used. Among them, from the viewpoint of improving oxygen absorbency and gas barrier properties and the viewpoint of ease of forming an inorganic vapor-deposited layer, the inorganic layer (II) is preferably a silicon oxide (silicon dioxide) vapor-deposited layer, an aluminum vapor-deposited layer or an aluminum oxide (alumina) vapor-deposited layer, and from the viewpoint of improving oxygen absorbency, an aluminum vapor-deposited layer is more preferred.

[0042] From the viewpoint of improving oxygen absorption and gas barrier properties, the thickness of the inorganic layer (II) is preferably 5 nm or more. In addition, from the viewpoint of improving bending resistance, it is preferably 20 μm or less, more preferably 10 μm or less, and when the inorganic layer (II) is an inorganic vapor-deposited layer, it is preferably 100 nm or less, more preferably 50 nm or less. The above thickness is the thickness of each layer of the inorganic layer (II).

[0043] The method for forming the inorganic layer (II) is not particularly limited. For example, the evaporation method may include physical vapor deposition methods such as vacuum evaporation, sputtering, and ion plating, or chemical vapor deposition methods such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition, and other well-known evaporation methods.

[0044] The inorganic layer (II) can be formed, for example, on the substrate (I) or on the cured product layer (III).

[0045] <Cured Material Layer (III)>

[0046] The cured product layer (III) used in the oxygen absorber of the present invention is a layer composed of a cured product of an epoxy resin composition containing an epoxy resin and an epoxy resin curing agent, wherein the epoxy resin curing agent includes an amine curing agent. The components contained in the epoxy resin composition are described below.

[0047] (Epoxy resin)

[0048] The epoxy resin used in the epoxy resin composition may be any of saturated or unsaturated aliphatic compounds, alicyclic compounds, aromatic compounds, or heterocyclic compounds. In view of exhibiting high oxygen absorbency and gas barrier properties, epoxy resins containing aromatic rings or alicyclic structures in the molecule are preferred.

[0049] Specific examples of the epoxy resin include at least one selected from the group consisting of epoxy resins having glycidylamino groups derived from m-xylylenediamine, epoxy resins having glycidylamino groups derived from p-xylylenediamine, epoxy resins having glycidylamino groups derived from 1,3-bis(aminomethyl)cyclohexane, epoxy resins having glycidylamino groups derived from 1,4-bis(aminomethyl)cyclohexane, epoxy resins having glycidylamino groups derived from diaminodiphenylmethane, epoxy resins having glycidylamino groups and / or glycidyloxy groups derived from p-aminophenol, epoxy resins having glycidyloxy groups derived from bisphenol A, epoxy resins having glycidyloxy groups derived from bisphenol F, epoxy resins having glycidyloxy groups derived from phenol novolac, and epoxy resins having glycidyloxy groups derived from resorcinol. The epoxy resins may be used alone or in combination of two or more.

[0050] Among the above, from the viewpoint of improving oxygen absorbency and gas barrier properties, the epoxy resin preferably contains as a main component at least one selected from the group consisting of an epoxy resin having a glycidyl amino group derived from m-xylylenediamine, an epoxy resin having a glycidyl amino group derived from p-xylylenediamine, and an epoxy resin having a glycidyl ether group derived from bisphenol F, and more preferably contains as a main component an epoxy resin having a glycidyl amino group derived from m-xylylenediamine.

[0051] It should be noted that the “main component” referred to herein may contain other components within the scope of the present invention, and is preferably 50 to 100% by mass, more preferably 70 to 100% by mass, and even more preferably 90 to 100% by mass of the whole.

[0052] (Epoxy resin curing agent including amine curing agent)

[0053] The epoxy resin curing agent used in the epoxy resin composition contains an amine curing agent from the viewpoint of improving oxygen absorbency and gas barrier properties.

[0054] As the amine curing agent, polyamines or modified products thereof conventionally used in epoxy resin curing agents can be used. From the viewpoint of improving oxygen absorbency and gas barrier properties, the amine curing agent is preferably a modified product of polyamine, and more preferably comprises a reaction product of the following (A) component and (B) component.

[0055] (A) at least one selected from the group consisting of m-xylylenediamine and p-xylylenediamine

[0056] (B) at least one selected from the group consisting of an unsaturated carboxylic acid represented by the following general formula (1) and its derivatives

[0057]

[0058] (In formula (1), R 1 , R 2 Each independently represents a hydrogen atom, an alkyl group having 1 to 8 carbon atoms, an aryl group having 6 to 12 carbon atoms, or an aralkyl group having 7 to 13 carbon atoms.)

[0059] From the viewpoint of improving oxygen absorbency and gas barrier properties, the component (A) is preferably meta-xylylenediamine.

[0060] The component (B) is at least one selected from the group consisting of unsaturated carboxylic acids represented by the general formula (1) and derivatives thereof. In order to improve oxygen absorption and gas barrier properties, R in the general formula (1) 1 It is preferably a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, more preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, further preferably a hydrogen atom or a methyl group, and still more preferably a hydrogen atom.

[0061] In addition, from the viewpoint of improving oxygen absorption and gas barrier properties, R in the above general formula (1) 2 It is preferably a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, more preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, further preferably a hydrogen atom or a methyl group, and still more preferably a hydrogen atom.

[0062] Examples of the derivatives of the unsaturated carboxylic acid represented by the general formula (1) include esters, amides, anhydrides and acid chlorides of the unsaturated carboxylic acid. The ester of the unsaturated carboxylic acid is preferably an alkyl ester, and the alkyl group preferably has 1 to 6 carbon atoms, more preferably 1 to 3 carbon atoms, and still more preferably 1 to 2 carbon atoms, from the viewpoint of obtaining good reactivity.

[0063] Examples of the unsaturated carboxylic acid represented by the general formula (1) and its derivatives include unsaturated carboxylic acids such as acrylic acid, methacrylic acid, α-ethylacrylic acid, α-propylacrylic acid, α-isopropylacrylic acid, α-n-butylacrylic acid, α-tert-butylacrylic acid, α-pentylacrylic acid, α-phenylacrylic acid, α-benzylacrylic acid, crotonic acid, 2-pentenoic acid, 2-hexenoic acid, 4-methyl-2-pentenoic acid, 2-heptenoic acid, 4-methyl-2-hexenoic acid, 5-methyl-2-hexenoic acid, 4,4-dimethyl-2-pentenoic acid, 4-phenyl-2-butenoic acid, cinnamic acid, o-methylcinnamic acid, m-methylcinnamic acid, p-methylcinnamic acid, and 2-octenic acid, and their esters, amides, anhydrides, acid chlorides, and the like.

[0064] Among the above, from the viewpoint of improving oxygen absorbency and gas barrier properties, the component (B) is preferably at least one selected from the group consisting of acrylic acid, methacrylic acid, crotonic acid and derivatives thereof, more preferably at least one selected from the group consisting of acrylic acid, methacrylic acid, crotonic acid and alkyl esters thereof, further preferably at least one selected from the group consisting of acrylic acid, methacrylic acid and alkyl esters thereof, further preferably an alkyl ester of acrylic acid, and still more preferably methyl acrylate.

[0065] The reaction between the component (A) and the component (B) is carried out by mixing the component (A) and the component (B) at 0 to 100° C., more preferably 0 to 70° C., and performing a Michael addition reaction and an amide group formation reaction based on dehydration, dealcoholization or deamination at 100 to 300° C., preferably 130 to 250° C., when an unsaturated carboxylic acid, ester or amide is used as the component (B).

[0066] At this time, when the amide group forms the reaction, in order to terminate the reaction, the reaction unit may be subjected to a decompression treatment in the final stage of the reaction as required. In addition, a non-reactive solvent may be used for dilution as required. Furthermore, a catalyst such as phosphite may be added as a dehydrating agent or a dealcoholizing agent.

[0067] On the other hand, when an anhydride or an acid chloride of an unsaturated carboxylic acid is used as the component (B), the Michael addition reaction and the amide group formation reaction are carried out by mixing at 0 to 150°C, preferably 0 to 100°C. At this time, in order to terminate the amide group formation reaction, the reaction apparatus may be decompressed in the final stage of the reaction as required. In addition, a non-reactive solvent may be used for dilution as required. Furthermore, a tertiary amine such as pyridine, picoline, lutidine, or a trialkylamine may be added.

[0068] Since the amide group site formed by the reaction of the aforementioned component (A) and the aforementioned component (B) has high cohesive force, the cured layer (III) formed using the reaction product of the components (A) and (B), i.e., the epoxy resin curing agent, has oxygen absorbency, gas barrier properties, and good adhesion.

[0069] The reaction molar ratio of the component (B) to the component (A) [(B) / (A)] is preferably in the range of 0.3 to 1.0. If the reaction molar ratio is 0.3 or more, a sufficient amount of amide groups will be generated in the epoxy resin curing agent, and a high level of gas barrier properties and adhesion will be exhibited. On the other hand, if the reaction molar ratio is in the range of 1.0 or less, the amount of amino groups required for the reaction with the epoxy group in the epoxy resin is sufficient, and the heat resistance and solubility in organic solvents or water are excellent.

[0070] From the viewpoint of oxygen absorbency and gas barrier properties of the obtained cured layer (III), the reaction molar ratio of the component (B) to the component (A) [(B) / (A)] is more preferably in the range of 0.6 to 1.0.

[0071] The amine curing agent may be a reaction product of the above-mentioned components (A) and (B) and at least one compound selected from the group consisting of the following components (C), (D) and (E).

[0072] (C) Select from R 3 At least one of the group consisting of monocarboxylic acids represented by -COOH and derivatives thereof (R 3 represents a hydrogen atom, an alkyl group having 1 to 7 carbon atoms or an aryl group having 6 to 12 carbon atoms which may have a hydroxyl group)

[0073] (D) Cyclic carbonate

[0074] (E) Monoepoxy compounds having 2 to 20 carbon atoms

[0075] The aforementioned component (C) is R 3 The monocarboxylic acid represented by -COOH and its derivatives are used as necessary from the viewpoint of reducing the reactivity between the epoxy resin curing agent and the epoxy resin and improving workability.

[0076] R 3 represents a hydrogen atom, an alkyl group having 1 to 7 carbon atoms or an aryl group having 6 to 12 carbon atoms which may have a hydroxyl group, and R 3 An alkyl group having 1 to 3 carbon atoms or a phenyl group is preferred.

[0077] In addition, as R 3Derivatives of monocarboxylic acids represented by -COOH include, for example, esters, amides, anhydrides and chlorides of the carboxylic acids. The esters of the carboxylic acids are preferably alkyl esters, and the alkyl group preferably has 1 to 6 carbon atoms, more preferably 1 to 3 carbon atoms, and even more preferably 1 to 2 carbon atoms.

[0078] Examples of the component (C) include monocarboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, lactic acid, glycolic acid, and benzoic acid, and derivatives thereof.

[0079] The (C) component may be used alone or in combination of two or more.

[0080] From the viewpoint of reducing the reactivity of epoxy resin curing agent and epoxy resin and improving workability, the aforementioned (D) component, i.e., cyclic carbonate, is used as required, and from the viewpoint of reactivity with the aforementioned (A) component, it is preferably a cyclic carbonate below a six-membered ring. For example, it can be listed: ethylene carbonate, propylene carbonate, glyceryl carbonate, carbonate-1,2-butylene ester, vinylene carbonate, 4-vinyl-1,3-dioxolane-2-one, 4-methoxymethyl-1,3-dioxolane-2-one, 1,3-dioxane-2-one, etc. Among them, from the viewpoint of gas barrier properties, it is preferably selected from at least one of the group consisting of ethylene carbonate, propylene carbonate and glyceryl carbonate.

[0081] The monoepoxy compound of the component (E) is a monoepoxy compound having 2 to 20 carbon atoms, and is used as required to reduce the reactivity between the epoxy resin curing agent and the epoxy resin and improve workability. From the viewpoint of gas barrier properties, a monoepoxy compound having 2 to 10 carbon atoms is preferred, and a compound represented by the following formula (2) is more preferred.

[0082]

[0083] (In formula (2), R 4 represents a hydrogen atom, an alkyl group having 1 to 8 carbon atoms, an aryl group, or R 5 -O-CH2-, R 5 represents phenyl or benzyl. )

[0084] Examples of the monoepoxy compound represented by the formula (2) include ethylene oxide, propylene oxide, 1,2-butylene oxide, styrene oxide, phenyl glycidyl ether, and benzyl glycidyl ether. The component (E) may be used alone or in combination of two or more.

[0085] When the component (C), component (D) or component (E) is used in the amine curing agent, any one compound selected from the group consisting of the components (C), (D) and (E) may be used alone or in combination of two or more.

[0086] It should be noted that the amine curing agent may be a reaction product obtained by reacting the components (A) to (E) as well as other components within a range that does not impair the effects of the present invention. Examples of the other components include aromatic dicarboxylic acids or derivatives thereof.

[0087] The amount of the "other components" used is preferably 30% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, of the total amount of the reactive components constituting the amine-based curing agent.

[0088] The reaction product of the aforementioned component (A) and component (B) and at least one compound selected from the group consisting of the aforementioned component (C), component (D) and component (E) can be obtained by combining at least one compound selected from the group consisting of the aforementioned component (C), component (D) and component (E) with the aforementioned component (B) and reacting the combination with the polyamine compound, i.e., the aforementioned component (A). In this reaction, the aforementioned components (B) to (E) can be added in any order and reacted with the aforementioned component (A), or the aforementioned components (B) to (E) can be mixed and reacted with the aforementioned component (A).

[0089] The reaction of the component (A) with the component (C) can be carried out under the same conditions as the reaction of the component (A) with the component (B). When the component (C) is used, the components (B) and (C) may be mixed and then reacted with the component (A), or the components (A) and (B) may be reacted first and then reacted with the component (C).

[0090] On the other hand, when the component (D) and / or the component (E) is used, it is preferred that the component (A) and the component (B) are reacted first and then reacted with the component (D) and / or the component (E).

[0091] The reaction of the component (A) with the component (D) and / or the component (E) is carried out by mixing the component (A) with the component (D) and / or the component (E) at 25 to 200° C. and performing an addition reaction at 30 to 180° C., preferably 40 to 170° C. In addition, a catalyst such as sodium methoxide, sodium ethoxide, potassium tert-butoxide, etc. may be used as necessary.

[0092] In the above reaction, in order to promote the reaction, the component (D) and / or the component (E) may be melted or diluted with a non-reactive solvent before use, as required.

[0093] When the amine curing agent is a reaction product of the components (A) and (B) and at least one compound selected from the group consisting of the components (C), (D) and (E), the reaction molar ratio of the component (B) to the component (A) [(B) / (A)] is preferably in the range of 0.3 to 1.0, and more preferably in the range of 0.6 to 1.0, for the same reasons as above. On the other hand, the reaction molar ratio of the components (C), (D) and (E) to the component (A) {[(C)+(D)+(E)] / (A)} is preferably in the range of 0.05 to 3.1, more preferably in the range of 0.07 to 2.5, and even more preferably in the range of 0.1 to 2.0.

[0094] Among them, from the viewpoints of oxygen absorbency, gas barrier properties and coating properties, the reaction molar ratio of the above-mentioned (B) to (E) components to the above-mentioned (A) component {[(B) + (C) + (D) + (E)] / (A)} is preferably in the range of 0.35 to 2.5, and more preferably in the range of 0.35 to 2.0.

[0095] From the viewpoint of improving oxygen absorbability, gas barrier properties and adhesiveness, the reaction product of the component (A) and the component (B), i.e., the amine curing agent, is preferably a reaction product obtained by reacting only the component (A) and the component (B), and more preferably a reaction product obtained by reacting only m-xylylenediamine and an alkyl acrylate.

[0096] In addition, from the viewpoint of improving oxygen absorbency, gas barrier properties and adhesion, the content of the reaction product of the above-mentioned component (A) and component (B) in the amine curing agent is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 90% by mass or more, and is 100% by mass or less.

[0097] The epoxy resin curing agent used in the present invention may also contain a curing agent component other than an amine curing agent. From the viewpoint of improving oxygen absorbency and gas barrier properties, a curing agent having a high content of an amine curing agent is preferred. From the viewpoint of improving oxygen absorbency and gas barrier properties, the content of the amine curing agent in the epoxy resin curing agent is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and even more preferably 90% by mass or more, and is 100% by mass or less.

[0098] Regarding the mixing ratio of the epoxy resin and the epoxy resin curing agent in the epoxy resin composition, it can be the standard mixing range in the case of preparing the epoxy resin reactant by the reaction of the epoxy resin and the epoxy resin curing agent. Specifically, the ratio of the number of active hydrogens in the epoxy resin curing agent to the number of epoxy groups in the epoxy resin (the number of active hydrogens in the epoxy resin curing agent / the number of epoxy groups in the epoxy resin) is preferably in the range of 0.2 to 12.0. From the viewpoint of improving oxygen absorbency, gas barrier properties and adhesion, (the number of active hydrogens in the epoxy resin curing agent / the number of epoxy groups in the epoxy resin) is more preferably 0.2 to 10.0, further preferably 0.2 to 8.0, further preferably 0.5 to 6.0, further preferably more than 1.0 and less than 5.0, further preferably 1.1 to 5.0, further preferably 2.0 to 5.0, further preferably 3.0 to 5.0, further preferably 3.5 to 5.0.

[0099] The epoxy resin composition may further contain a coupling agent from the viewpoint of improving the adhesion of the obtained cured layer (III) to the inorganic layer (II). Examples of the coupling agent include silane coupling agents, titanate coupling agents, and aluminate coupling agents, and silane coupling agents are preferred.

[0100] Examples of the silane coupling agent include silane coupling agents having a vinyl group, silane coupling agents having an amino group, silane coupling agents having an epoxy group, silane coupling agents having a (meth)acryloyl group, silane coupling agents having a mercapto group, etc. Among them, from the viewpoint of improving the adhesion between the obtained cured layer (III) and the inorganic layer (II), at least one selected from the group consisting of silane coupling agents having an amino group and silane coupling agents having an epoxy group is preferred.

[0101] When a coupling agent is used, the content of the coupling agent in the epoxy resin composition is preferably 0.1 to 10 parts by mass, more preferably 1 to 8 parts by mass, based on 100 parts by mass of the epoxy resin curing agent.

[0102] The epoxy resin composition may contain additives such as a thermosetting resin, a wetting agent, a tackifier, a defoaming agent, a curing accelerator, a rust-proofing additive, a pigment, and an oxygen scavenger as needed within a range not impairing the effects of the present invention.

[0103] When using additives, the total content of the additives in the epoxy resin composition is preferably 20.0 parts by mass or less, more preferably 0.001 to 15.0 parts by mass, based on 100 parts by mass of the total amount of the epoxy resin and the epoxy resin curing agent.

[0104] Among them, from the viewpoint of obtaining the effect of the present invention, the total content of the epoxy resin and the epoxy resin curing agent in the solid content of the epoxy resin composition is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and further preferably 85% by mass or more, and is 100% by mass or less. The "solid content of the epoxy resin composition" refers to the components after removing water and organic solvents in the epoxy resin composition.

[0105] The epoxy resin composition may contain an organic solvent, and a non-reactive solvent is preferably used as the organic solvent. As specific examples thereof, one or more of the following solvents may be used: protic polar solvents such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 2-methoxyethanol, 2-ethoxyethanol, 2-propoxyethanol, 2-butoxyethanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, 1-propoxy-2-propanol, and ethyl acetate, butyl acetate, methyl isobutyl ketone, toluene, and the like.

[0106] Among the above, at least one selected from the group consisting of methanol, ethanol and ethyl acetate is preferred from the viewpoint of improving the drying rate.

[0107] In the epoxy resin composition, the content of the lubricant is preferably small from the viewpoint that the obtained cured product layer (III) exhibits higher adhesiveness. Specifically, the content of the lubricant in the epoxy resin composition is preferably less than 10 parts by mass, more preferably less than 5 parts by mass, further preferably less than 2 parts by mass, further preferably less than 1 part by mass, further preferably less than 0.1 parts by mass, further preferably less than 0.01 parts by mass, further preferably 0 parts by mass, relative to 100 parts by mass of the total amount of the epoxy resin and the epoxy resin curing agent in the epoxy resin composition.

[0108] The lubricant contains, in addition to conventionally known components as lubricants, unsaturated fatty acid amides having 14 to 24 carbon atoms, such as erucamide and oleamide.

[0109] From the viewpoint that the obtained cured product layer (III) exhibits higher adhesiveness, the epoxy resin composition preferably has a small content of fillers such as organic or inorganic powders and organic or inorganic fibers. Specifically, the content of the filler in the epoxy resin composition is preferably less than 10 parts by mass, more preferably less than 5 parts by mass, further preferably less than 2 parts by mass, further preferably less than 1 part by mass, further preferably less than 0.1 parts by mass, further preferably less than 0.01 parts by mass, and further preferably 0 parts by mass, relative to 100 parts by mass of the total amount of the epoxy resin and the epoxy resin curing agent in the epoxy resin composition.

[0110] The epoxy resin composition can be prepared by, for example, mixing the epoxy resin, the epoxy resin curing agent, and, if necessary, the additives and the solvent in predetermined amounts, respectively, and then stirring and mixing the mixture using a known method and apparatus.

[0111] The method for curing the epoxy resin composition to form the cured product layer (III) will be described later in the method for producing the oxygen absorbent.

[0112] From the viewpoint of improving oxygen absorbency and gas barrier properties, the thickness of the cured layer (III) is preferably 0.1 μm or more, more preferably 0.5 μm or more, further preferably 1 μm or more, and further preferably 1.5 μm or more. In addition, from the viewpoint of improving adhesion, it is preferably 20 μm or less, more preferably 10 μm, and further preferably 5 μm or less. The above thickness is the thickness of each cured layer (III).

[0113] The oxygen absorber of the present invention may have any layer other than the substrate (I), the inorganic layer (II) and the cured layer (III), such as an adhesive layer, a primer layer, an ink layer, a surface protective layer, etc. The inorganic layer (II) and the cured layer (III) need to be adjacent to each other, and there is no layer between the inorganic layer (II) and the cured layer (III).

[0114] For the oxygen absorbing material of the present invention, in order to express oxygen absorbing properties through the inorganic layer (II) and the cured layer (III), it is preferred that there is no oxygen absorbing layer other than the inorganic layer (II) and the cured layer (III). As the oxygen absorbing layer, for example, a polyamide resin layer containing a polyamide resin and a transition metal can be cited. Transition metals refer to elements of Groups 3 to 11 in the periodic table, generally inorganic acid salts, organic acid salts, or compounds that promote oxygen absorbing properties by being included in the polyamide resin layer in the form of complex salts. Examples of such transition metals include cobalt, copper, cerium, manganese, iron, chromium, and nickel.

[0115] Furthermore, any layer constituting the oxygen absorber of the present invention preferably does not contain the above transition metals. Specifically, the total content of transition metals in the oxygen absorber of the present invention is preferably less than 5 ppm, more preferably less than 3 ppm, further preferably less than 1 ppm, and further preferably less than 0.1 ppm.

[0116] The total thickness of the oxygen absorber varies depending on the layer constitution, but is preferably 6 to 600 μm, more preferably 10 to 500 μm, further preferably 20 to 300 μm, and further preferably 20 to 200 μm from the viewpoint of improving oxygen absorbency and gas barrier properties.

[0117] <Method for producing oxygen absorbent material>

[0118] The method for producing the oxygen absorber of the present invention is not particularly limited, and a known method can be used.

[0119] For example, as a method for producing an oxygen absorber in which a substrate (I), an inorganic layer (II) and a cured product layer (III) are sequentially stacked, there can be cited a method in which an inorganic layer (II) is formed on one side of a substrate (I), the aforementioned epoxy resin composition is applied to the inorganic layer (II) in a manner to obtain a desired thickness, and then the epoxy resin composition is cured to form a cured product layer (III). It should be noted that a thin film in which an inorganic layer (II) is preliminarily formed on a substrate (I) can also be used, and a cured product layer (III) can be formed on the inorganic layer (II).

[0120] As a method for producing an oxygen absorber in which a substrate (IA), an inorganic layer (II), a cured layer (III), and a substrate (IB) are sequentially stacked, there can be cited a method in which an inorganic layer (II) is formed on one surface of a substrate (IA), the aforementioned epoxy resin composition is applied to the inorganic layer (II) in a manner to a desired thickness, the coated surface is bonded to the substrate (IB), and then the epoxy resin composition is cured to form a cured layer (III).

[0121] As the coating method when applying the epoxy resin composition, for example, rod coating, Meyer rod coating, air knife coating, gravure coating, reverse gravure coating, micro gravure coating, micro reverse gravure coating, die coating, slot die coating, vacuum die coating, dip coating, spin coating, roll coating, spray coating, brush coating, etc. Among them, rod coating, roll coating or spray coating is preferred, and gravure coating, reverse gravure coating, micro gravure coating or micro reverse gravure coating is industrially preferred.

[0122] After the epoxy resin composition is applied, a step of volatilizing the solvent (drying step) is performed as needed. The conditions in the drying step can be appropriately selected, and for example, the drying step can be performed at a drying temperature of 60 to 180° C. and a drying time of 5 to 180 seconds.

[0123] After the drying step, the epoxy resin composition is cured to form a cured product layer (III). The curing temperature can be selected, for example, in the range of 10 to 140° C., preferably in the range of 10 to 80° C. In addition, the curing time can be selected, for example, in the range of 0.5 to 200 hours, preferably in the range of 2 to 100 hours.

[0124] <Characteristics of oxygen absorbent materials>

[0125] The oxygen absorber of the present invention has oxygen absorbability and excellent gas barrier properties. For example, the oxygen permeability of the oxygen absorber at 23°C and a relative humidity of 60% varies depending on the barrier properties of the substrate (I) and the inorganic layer (II) used, but is preferably 1cc (m 2·day·atm) or less, more preferably 0.8cc / (m 2 ·day·atm) or less, more preferably 0.6cc / (m 2 ·day·atm) or less, and more preferably 0.3cc / (m 2 ·day·atm) or less.

[0126] The oxygen permeability of the oxygen absorbing material can be specifically measured by the method described in Examples.

[0127] <Shape and usage of oxygen absorber>

[0128] The shape of the oxygen absorber of the present invention can be appropriately selected according to the usage form, for example, it can be a sheet shape or a bag shape. As the usage of the oxygen absorber, there can be cited a method of sealing the film-shaped oxygen absorber inside a packaging material such as a container or a packaging bag; a method of using the oxygen absorber as a packaging material, etc.

[0129] [How to store items]

[0130] The method for storing articles of the present invention is a method for storing articles using the oxygen absorbent material, and the method includes any one or more of the following (1) and (2).

[0131] (1) The aforementioned article is placed in a packaging material enclosing the aforementioned oxygen absorbing material.

[0132] (2) The aforementioned article is placed in a packaging material, wherein the packaging material has the aforementioned oxygen absorbing material in at least a portion thereof, and the oxygen permeability of the packaging material is 1 cc / (m 2 ·day·atm) or less.

[0133] Since the oxygen absorbing material has oxygen absorbing properties, the method for storing an article according to the present invention (hereinafter referred to as "the method of the present invention") can effectively suppress oxidative degradation of the article to be stored.

[0134] In the aspect of (1) above, the article is housed in the packaging material in which the oxygen absorbing material is sealed.

[0135] The oxygen absorber used in the embodiment (1) may be in any shape that can be enclosed in a packaging material, and is preferably in the form of a sheet. The oxygen absorber may be attached to the packaging material or may be enclosed in the packaging material in a state of being stored in a packaging bag.

[0136] The form of the packaging material used in the above-mentioned method (1) can be appropriately selected according to the items to be stored and preserved, for example, packaging films; packaging containers such as packaging bags and bottles; and lid materials and sealing materials for packaging containers. Specific examples of packaging films or packaging bags include three-side sealed flat bags, self-supporting bags, gusseted packaging bags, pillow packaging bags, multi-chamber bags consisting of a main chamber and a sub-chamber with an easily peelable wall between the main chamber and the sub-chamber, shrink film packaging, etc. There are no particular restrictions on the thickness and capacity of the packaging material, and they can be appropriately selected according to the items to be stored.

[0137] The material of the packaging material used in the embodiment (1) is not particularly limited, but is preferably a packaging material having gas barrier properties. For example, when the packaging material is a packaging bag, examples thereof include aluminum packaging bags and packaging bags using a plastic substrate having a transparent vapor-deposited layer.

[0138] In the above-mentioned embodiment (2), the above-mentioned article is contained in a packaging material, the packaging material has the above-mentioned oxygen absorbing material in at least a part thereof, and the oxygen permeability of the packaging material is 1cc / (m 2 From the viewpoint of effectively suppressing oxidative degradation of the article, it is preferred that the packaging material is a packaging material composed of the above-mentioned oxygen absorbing material.

[0139] The oxygen permeability of the packaging material used in the above embodiment (2) is a value measured by the method described in the examples at 23°C and a relative humidity of 60%, and is preferably 0.8 cc / (m 2 ·day·atm), more preferably 0.6cc / (m 2 ·day·atm) or less, more preferably 0.3cc / (m 2 ·day·atm) or less.

[0140] From the viewpoint of having the oxygen absorber in at least a portion thereof, the packaging material used in the above-mentioned embodiment (2) is preferably in the form of a packaging film or a packaging bag, and its specific examples are the same as those described in the above-mentioned embodiment (1). The thickness and capacity of the packaging material are not particularly limited and can be appropriately selected according to the items to be stored.

[0141] The method of the present invention may be a method including the above-mentioned aspects (1) and (2).

[0142] The articles to be stored in the method of the present invention include foods, beverages, seasonings, chemicals, pharmaceuticals, cosmetics, pet foods, lotions, etc. The articles preferably contain water because water serves as a trigger to increase the oxygen absorbency of the oxygen absorbent.

[0143] For example, when the object to be stored is food, the water activity (Aw) of the food is preferably 0.75 or more, more preferably 0.80 or more, further preferably 0.85 or more, further preferably 0.90 or more, and further preferably 0.95 or more, from the viewpoint that water serves as a trigger to improve the oxygen absorbency of the oxygen absorber. Here, the water activity Aw of the food is defined as the ratio of the water vapor pressure P in the closed system containing the food to the vapor pressure PO of pure water at the temperature, which is Aw=P / PO.

[0144] The water activity Aw of a food is represented by Aw=RH / 100, where the relative humidity in a closed system containing the food is RH (%).

[0145] In the method of the present invention, from the viewpoint of improving the oxygen absorbency of the oxygen absorbent, the temperature inside the packaging material containing the article is preferably 5°C or higher, more preferably 10°C or higher, further preferably 25°C or higher, and usually 80°C or lower.

[0146] Alternatively, in the method of the present invention, the packaging material containing the article is stored at preferably 5°C or higher, more preferably 10°C or higher, further preferably 25°C or higher, and usually 80°C or lower.

[0147] In the method of the present invention, from the viewpoint of improving the oxygen absorbency of the oxygen absorbent, the relative humidity in the packaging material containing the article is preferably 85% or more, more preferably 90% or more, and even more preferably 95% or more and 100% or less.

[0148] Alternatively, in the method of the present invention, the packaging material containing the article is preferably stored under an environment with a relative humidity of 85% or more, more preferably 90% or more, and even more preferably 95% or more and 100% or less.

[0149] [application]

[0150] The present invention also provides an application of a laminate as an oxygen absorbing material, the laminate comprising: a substrate (I), an inorganic layer (II) and a cured layer (III) of an epoxy resin composition containing an epoxy resin and an epoxy resin curing agent, wherein the epoxy resin curing agent includes an amine curing agent, and the aforementioned inorganic layer (II) is adjacent to the aforementioned cured layer (III).

[0151] The details of the substrate (I), the inorganic layer (II), the cured product layer (III) and the laminate and their preferred embodiments are the same as those described in the above-mentioned oxygen absorber.

[0152] Example

[0153] Next, the present invention will be specifically described by way of examples, but the present invention is not limited by these examples in any way.

[0154] In the present examples, measurements and evaluations were performed by the following methods.

[0155] <Thickness of Cured Material Layer>

[0156] The measurement was performed using a multilayer film thickness measuring device ("DC-8200" manufactured by GUNZE LIMITED).

[0157] <Oxygen absorption (cc / g)>

[0158] The thin film oxygen absorber obtained in each example was cut to prepare four 5 cm × 15 cm strip test pieces. These were placed in an aluminum bag of about 21 cm × 15 cm, and then 200 cc of air was sealed in the bag. After the bag was humidified to the humidity recorded in the table, it was sealed. After the aluminum bag was stored at the temperature recorded in the table for a specified period of time, the oxygen concentration in the bag was measured using a zirconium dioxide oxygen concentration measuring device ("LC-750F" manufactured by TORAY ENGINEERING Co., Ltd.), and the oxygen absorption amount of each oxygen absorber was calculated.

[0159] Manufacturing Example 1 (Preparation of epoxy resin curing agent solution A)

[0160] 1 mol of m-xylylenediamine (MXDA) was added to the reaction vessel. The temperature was raised to 60°C under a nitrogen stream, and 0.93 mol of methyl acrylate was added dropwise over 1 hour. The generated methanol was distilled off while the temperature was raised to 165°C, and the temperature was maintained at 165°C for 2.5 hours to obtain an amine curing agent. Methanol was added dropwise over 1.5 hours, and 3-aminopropyltriethoxysilane ("KBE-903" manufactured by Shin-Etsu Chemical Co., Ltd.) as a silane coupling agent was added to obtain an epoxy resin curing agent solution A with 62.2% by mass of amine curing agent, 2.8% by mass of 3-aminopropyltriethoxysilane, and 35% by mass of methanol.

[0161] Production Example 2 (Preparation of epoxy resin composition A)

[0162] 2.15 g of methanol and 3.25 g of ethyl acetate were added as diluents, and the mixture was stirred thoroughly. Then, 3.13 g of the epoxy resin curing agent solution A obtained in Production Example 1 was added and stirred. 1.46 g of an epoxy resin having a glycidylamino group derived from meta-xylylenediamine ("TETRAD-X" manufactured by Mitsubishi Gas Chemical Co., Ltd.) was added as an epoxy resin (the number of active hydrogens in the epoxy resin curing agent / the number of epoxy groups in the epoxy resin = 0.8) and stirred to prepare an epoxy resin composition A.

[0163] Production Example 3 (Preparation of epoxy resin composition B)

[0164] In Production Example 2, epoxy resin composition B was prepared by the same method as in Production Example 2, except that the amount of methanol as a dilution solvent was changed to 1.98 g, the amount of the epoxy resin curing agent solution A obtained in Production Example 1 was changed to 3.64 g, and the amount of the epoxy resin having a glycidylamino group derived from meta-xylylenediamine ("TETRAD-X" manufactured by Mitsubishi Gas Chemical Co., Ltd.) was changed to 1.13 g (the number of active hydrogens in the epoxy resin curing agent / the number of epoxy groups in the epoxy resin = 1.2).

[0165] Production Example 4 (Preparation of Epoxy Resin Composition C)

[0166] In Production Example 2, an epoxy resin composition C was prepared by the same method as in Production Example 2, except that the amount of methanol as a dilution solvent was changed to 1.56 g, the amount of the epoxy resin curing agent solution A obtained in Production Example 1 was changed to 4.83 g, and the amount of the epoxy resin having a glycidylamino group derived from meta-xylylenediamine (“TETRAD-X” manufactured by Mitsubishi Gas Chemical Co., Ltd.) was changed to 0.36 g (the number of active hydrogens in the epoxy resin curing agent / the number of epoxy groups in the epoxy resin = 5.0).

[0167] Production Example 5 (Preparation of epoxy resin composition D)

[0168] In Production Example 2, an epoxy resin composition D was prepared by the same method as in Production Example 2, except that the amount of methanol as a dilution solvent was changed to 3.62 g, the amount of ethyl acetate was changed to 4.30 g, the amount of the epoxy resin curing agent solution A obtained in Production Example 1 was changed to 1.93 g, and the amount of the epoxy resin having a glycidylamino group derived from meta-xylylenediamine ("TETRAD-X" manufactured by Mitsubishi Gas Chemical Co., Ltd.) was changed to 0.14 g (the number of active hydrogens in the epoxy resin curing agent / the number of epoxy groups in the epoxy resin = 5.0).

[0169] Production Example 6 (Preparation of Epoxy Resin Composition E)

[0170] In Production Example 2, an epoxy resin composition E was prepared by the same method as in Production Example 2 except that the amount of methanol as a dilution solvent was changed to 2.47 g, the amount of the epoxy resin curing agent solution A obtained in Production Example 1 was changed to 2.20 g, and 0.31 g (the number of active hydrogens in the epoxy resin curing agent / the number of epoxy groups in the epoxy resin=5.0) of a multifunctional epoxy resin having a glycidyl ether group derived from bisphenol A ("jER828" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 186 g / equivalent) was used instead of the epoxy resin having a glycidyl amino group derived from meta-xylylenediamine ("TETRAD-X" manufactured by Mitsubishi Gas Chemical Co., Ltd.).

[0171] Production Example 7 (Preparation of Epoxy Resin Composition F)

[0172] In Production Example 2, an epoxy resin composition F was prepared by the same method as in Production Example 2 except that the amount of methanol as a dilution solvent was changed to 2.40 g, the amount of the epoxy resin curing agent solution A obtained in Production Example 1 was changed to 2.40 g, and 0.18 g of an epoxy resin having a glycidyl amino group derived from 1,3-bis(aminomethyl)cyclohexane (“TETRAD-C” manufactured by Mitsubishi Gas Chemical Co., Ltd.) was used instead of the epoxy resin having a glycidyl amino group derived from m-xylylenediamine (“TETRAD-X” manufactured by Mitsubishi Gas Chemical Co., Ltd.) (the number of active hydrogens in the epoxy resin curing agent / the number of epoxy groups in the epoxy resin = 5.0).

[0173] Example 1 (Production and Evaluation of Oxygen Absorbing Material)

[0174] The epoxy resin composition A obtained in Production Example 2 was applied to the aluminum-deposited surface of an unstretched polypropylene (CPP) film ("Cemilight SF-1", manufactured by Nakai Industry Co., Ltd., thickness 25 μm) in which aluminum was deposited on one side thereof, using a No. 8 coating bar. The epoxy resin composition was heated at 80° C. for 10 seconds to dry it (thickness after drying: 3 μm). A biaxially stretched polypropylene (OPP) film ("FOR", manufactured by FUTAMURA CHEMICAL CO., LTD., thickness 20 μm) was laminated thereto by nip rolls and heated at 40° C. for 2 days to obtain an oxygen absorber having the layer structure described in Table 1.

[0175] The oxygen absorption amount was measured by the aforementioned method using the oxygen absorbing material. In the measurement of the oxygen absorption amount, the humidity in the aluminum bag was adjusted by sealing absorbent cotton containing water in the bag. The results are shown in Table 1. In the following table, "A / E" refers to the number of active hydrogens in the epoxy resin curing agent / the number of epoxy groups in the epoxy resin.

[0176] Embodiments 2 to 4

[0177] In Example 1, an oxygen absorber was prepared by the same method as in Example 1 except that the epoxy resin composition was changed to that described in Table 1, and the oxygen absorption amount was measured by the above method.

[0178] Comparative Example 1

[0179] In Example 1, an oxygen absorber was prepared by the following method using a urethane adhesive instead of the epoxy resin composition A. The urethane adhesive was prepared by adding 0.8 g of a curing agent CAT-RT37-0.8K and 38.7 g of a solvent ethyl acetate to 17 g of a main agent TM-569 and stirring well.

[0180] The urethane adhesive was applied to the aluminum-deposited surface of the aluminum-deposited CPP using a No. 12 coating bar and dried at 80°C for 10 seconds to form an adhesive layer (thickness after drying: 3 μm). The OPP film having a thickness of 20 μm was laminated thereon using a nip roll and heated at 40°C for 2 days to obtain an oxygen absorber having the layer structure described in Table 1.

[0181] The oxygen absorption amount was measured using the oxygen absorbent material in the same manner as above. In the measurement of the oxygen absorption amount, the humidity in the aluminum bag was controlled by sealing absorbent cotton containing water in the bag. The results are shown in Table 1.

[0182] [Table 1]

[0183]

[0184] As can be seen from Table 1, the oxygen absorber of the present invention has a more excellent oxygen absorbency than the oxygen absorber of the comparative example. In addition, as can be seen from the comparison of Examples 1 to 3, in the epoxy resin composition used in the cured layer, when the number of active hydrogen in the epoxy resin curing agent / the number of epoxy groups in the epoxy resin is in the range of 1.2 to 5.0, the oxygen absorption amount is further increased.

[0185] Example 5

[0186] The epoxy resin composition A obtained in Production Example 2 was applied to the aluminum-deposited surface of aluminum-deposited PET (ML-PET manufactured by Mitsui Chemicals Tohcello, Inc., thickness 12 μm) having aluminum deposited on one side of a polyethylene terephthalate (PET) film using a No. 8 coating bar. The epoxy resin composition was heated at 80° C. for 10 seconds to dry it (thickness after drying: 3 μm). An unstretched polypropylene (CPP) film (P1146 manufactured by Toyobo Co., Ltd., thickness 50 μm) was laminated thereto by a nip roll and heated at 40° C. for 2 days to obtain an oxygen absorber having the layer structure described in Table 2.

[0187] The oxygen absorption amount was measured by the above method using the oxygen absorbent. In the measurement of the oxygen absorption amount, the humidity in the aluminum bag was adjusted by sealing absorbent cotton containing water in the bag. The results are shown in Table 2.

[0188] Example 6

[0189] In Example 5, an oxygen absorber was prepared in the same manner as in Example 5 except that the epoxy resin composition C obtained in Production Example 4 was used instead of the epoxy resin composition A, and the oxygen absorption amount was measured by the above method.

[0190] Example 7

[0191] In Example 5, an oxygen absorber was prepared by the same method as in Example 5 except that aluminum-deposited OPP (ML-OP102 manufactured by Mitsui Chemicals Tohcello, Inc., thickness 12 μm) in which aluminum was deposited on one side of a stretched polypropylene (OPP) film was used instead of aluminum-deposited PET, and the oxygen absorption amount was measured by the above method. The results are shown in Table 2.

[0192] Example 8

[0193] In Example 6, an oxygen absorber was prepared by the same method as in Example 6 except that the aluminum-deposited OPP was used instead of the aluminum-deposited PET, and the oxygen absorption amount was measured by the above method.

[0194] [Table 2]

[0195]

[0196] Example 9

[0197] The epoxy resin composition A obtained in Production Example 2 was applied to the alumina-deposited surface of alumina-deposited PET (Barrialox 1011HG, manufactured by TORAYADVANCED FILM CO., LTD., with a thickness of 12 μm) on one side of a polyethylene terephthalate (PET) film having alumina deposited thereon, using a No. 8 coating bar. The epoxy resin composition was heated at 80° C. for 10 seconds to dry it (thickness after drying: 3 μm). An unstretched polypropylene (CPP) film (P1146, manufactured by Toyobo Co., Ltd., with a thickness of 50 μm) was laminated thereto by a nip roll and heated at 40° C. for 2 days to obtain an oxygen absorber having the layer structure described in Table 3.

[0198] The oxygen absorption amount was measured by the above method using this oxygen absorbent. In the measurement of the oxygen absorption amount, the humidity in the aluminum bag was controlled by sealing absorbent cotton containing water in the bag. The results are shown in Table 3.

[0199] Example 10

[0200] In Example 9, an oxygen absorber was prepared in the same manner as in Example 9 except that the epoxy resin composition C obtained in Production Example 4 was used instead of the epoxy resin composition A, and the oxygen absorption amount was measured by the above method.

[0201] Embodiment 11

[0202] In Example 9, an oxygen absorber was prepared by the same method as in Example 9 except that a silica-deposited PET ("Techbarrier TCBL" manufactured by Mitsubishi Chemical Group Corporation, thickness 12 μm) in which silica was deposited on one side of a polyethylene terephthalate (PET) film was used instead of alumina-deposited PET, and the oxygen absorption amount was measured by the above method. The results are shown in Table 3.

[0203] Example 12

[0204] In Example 10, an oxygen absorber was prepared by the same method as in Example 10 except that the silica-deposited PET was used instead of the alumina-deposited PET, and the oxygen absorption amount was measured by the above method.

[0205] [Table 3]

[0206]

[0207] Table 2 shows examples in which the types of substrates (IA) and (IB) constituting the oxygen absorber are changed, and Table 3 shows examples in which the type of inorganic layer (II) constituting the oxygen absorber is changed.

[0208] As can be seen from Table 2, regarding the combination of substrates (IA) and (IB), the compositions of Examples 1 and 3 can increase the oxygen absorption the most. In addition, as can be seen from Table 3, when the inorganic layer (II) is an aluminum vapor-deposited layer, the oxygen absorption is increased compared to the cases of an aluminum oxide vapor-deposited layer and a silicon dioxide vapor-deposited layer.

[0209] Embodiment 13

[0210] The oxygen absorption amount was measured in the same manner as in Example 1 except that the storage temperature of the oxygen absorber was changed to 23° C. The results are shown in Table 4.

[0211] Embodiment 14

[0212] The oxygen absorption amount was measured in the same manner as in Example 3 except that the storage temperature of the oxygen absorber was changed to 23° C. The results are shown in Table 4.

[0213] [Table 4]

[0214]

[0215] As can be seen from Table 4, the amount of oxygen absorption increases when the storage temperature of the oxygen absorber is 40°C, compared to when the storage temperature of the oxygen absorber is 23°C.

[0216] Examples 15 to 20

[0217] The oxygen absorption amount was measured by the same method as in Example 3 except that the oxygen absorbent prepared in Example 3 was used and the humidity in the aluminum bag was adjusted to the humidity described in Table 5 using water and glycerin.

[0218] [Table 5]

[0219]

[0220] As can be seen from Table 5, when the humidity during storage of the oxygen absorber is high, the amount of oxygen absorbed increases.

[0221] Embodiment 21

[0222] Example 21 is an example showing the use of aluminum foil as the inorganic layer (II).

[0223] The aforementioned urethane adhesive (prepared by adding 0.8 g of curing agent CAT-RT37-0.8K and 38.7 g of solvent ethyl acetate to 17 g of main agent TM-569 and stirring thoroughly) was applied to one side of a polyethylene terephthalate film (thickness 12 μm) using a No. 12 coating rod, and dried at 80°C for 10 seconds to form an adhesive layer (thickness after drying: 3 μm). An aluminum foil with a thickness of 7 μm was bonded thereto by a nip roller. Then, the epoxy resin composition C obtained in Preparation Example 4 was applied to the aluminum foil surface using a No. 8 coating rod, and heated at 80°C for 10 seconds to dry it (thickness after drying: 3 μm). An unstretched polypropylene (CPP) film ("P1146" manufactured by Toyobo Co., Ltd., thickness 50 μm) was bonded thereto by a nip roller, and heated at 40°C for 2 days to obtain an oxygen absorber having the layer structure described in Table 6. Using this oxygen absorber, the oxygen absorption amount was measured by the aforementioned method. The results are shown in Table 6.

[0224] [Table 6]

[0225]

[0226] Embodiments 22-23

[0227] In Example 3, an oxygen absorber was prepared by the same method as in Example 3 except that the epoxy resin composition shown in Table 7 was used, and the oxygen absorption amount was measured by the above method.

[0228] [Table 7]

[0229]

[0230] Example 24 (Preservation method)

[0231] A white ink (a film obtained by diluting "Belle Flora R115" manufactured by Sakata Inx Corporation by 2 times with a diluting solvent ("L solvent" manufactured by Sakata Inx Corporation)) was applied to one side of a biaxially stretched polypropylene (OPP) film ("FOR" manufactured by Futamura Chemical Co., Ltd., thickness 20 μm) using a No. 8 coating bar, and dried by heating at 80°C for 10 seconds (thickness after drying: about 0.5 μm) to form a colored layer. A gravure ink for reverse printing (a film obtained by diluting "Belle Flora R Medium" manufactured by Sakata Inx Corporation by 2 times with a diluting solvent ("K solvent" manufactured by Sakata Inx Corporation)) was applied to the colored layer using a No. 8 coating bar, and dried by heating at 80°C for 10 seconds (thickness after drying: about 0.5 μm) to form a medium layer.

[0232] The epoxy resin composition C obtained in Production Example 4 was applied to the dielectric layer using a No. 8 coating bar, and dried by heating at 80°C for 10 seconds (thickness after drying: 3 μm). The coated surface of the epoxy resin composition and the aluminum-deposited surface of an unstretched polypropylene (CPP) film ("Cemilight SF-1" manufactured by Nakai Industry Co., Ltd., thickness 25 μm) in which aluminum was deposited on one side were overlapped and bonded by nip rolls, and heated at 40°C for 2 days to obtain an oxygen absorber having a structure in which CPP film (substrate (IA)) / aluminum-deposited layer (II) / cured material layer (III) / dielectric layer / coloring layer / OPP film (substrate (IB)) were stacked in this order.

[0233] The oxygen absorbing material was bagged so that the substrate (IA) side was on the inner side to prepare a bag-shaped packaging material. The oxygen absorbing material constituting the packaging material had an oxygen permeability of 0.09 cc / (m 2 ·day·atm). The oxygen permeability is measured by the method described below.

[0234] Store rice cakes in bag-shaped packaging materials ( Figure 1 The packaging material was sealed and stored at 40°C and 90% relative humidity for 2 months. The initial oxygen content in the packaging material was 10cc, and the initial oxygen concentration in the packaging material was 20.8%. After 2 months of storage, the appearance of the rice cake was visually observed, and no changes in appearance were observed ( Figure 1 (b)).

[0235] <Measurement of oxygen permeability>

[0236] The oxygen permeability was measured under the conditions of 23° C. and a relative humidity of 60% using an oxygen permeability measuring apparatus (“OX-TRAN 2 / 21” manufactured by Modern Control).

[0237] Comparative Example 2

[0238] In Example 24, the rice cake was preserved in the same manner as in Example 24 except that the aforementioned urethane adhesive (prepared by adding 0.8 g of curing agent CAT-RT37-0.8K and 38.7 g of solvent ethyl acetate to 17 g of main agent TM-569 and stirring thoroughly) was used instead of the epoxy resin composition C obtained in Preparation Example 4. The oxygen permeability of the oxygen absorbing material constituting the packaging material was 2.7 cc / (m 2 ·day·atm). After 2 months of storage, the appearance of the rice cakes was visually observed and mold growth was found ( Figure 1 (c)).

[0239] Comparative Example 3

[0240] The aforementioned urethane adhesive was applied to one side of an aluminum foil (7 μm thick) using a No. 12 coating rod, and dried at 80° C. for 10 seconds to form an adhesive layer (thickness after drying: 3 μm). A PET film (E5100 manufactured by Toyobo Co., Ltd., 12 μm thick) was laminated thereon by a nip roller, and heated at 40° C. for 2 days to obtain a laminated film having a structure in which aluminum foil (II) / urethane adhesive layer / PET film were laminated in this order. Then, the aforementioned polyurethane adhesive was applied to the aluminum foil side of the laminated film using a No. 12 coating rod, and dried at 80° C. for 10 seconds to form an adhesive layer (thickness after drying: 3 μm). An unstretched polypropylene (CPP) film ("P1146" manufactured by Toyobo Co., Ltd., thickness 50 μm) was laminated thereon by nip rollers and heated at 40°C for 2 days to obtain a laminate having a structure in which CPP / urethane adhesive layer / aluminum foil (II) / urethane adhesive layer / PET film were laminated in sequence. The laminate was bagged in such a way that the aluminum foil (II) side became the inner side to produce a bag-shaped packaging material. The oxygen permeability of the laminate constituting the packaging material was 0.01 cc / (m2 ·day·atm) or less.

[0241] Store rice cakes in bag-shaped packaging materials ( Figure 1 The packaging material was sealed at 40°C and 90% relative humidity for 2 months in the same manner as in Example 24. The initial oxygen content in the packaging material was 10 cc, and the initial oxygen concentration in the packaging material was 20.8%. After 2 months of storage, the appearance of the rice cake was visually observed, and mold growth was found ( Figure 1 (d)).

[0242] In Comparative Example 3, mold still grew in the rice cake, the content, despite the use of packaging materials with high oxygen barrier properties. This is believed to be because the packaging materials used did not exhibit oxygen absorption properties, so the residual oxygen in the packaging materials caused the content to deteriorate.

[0243] Embodiment 25

[0244] In Example 24, the article contained in the packaging material was changed to cheese cod ( Figure 2 The storage stability was evaluated by the same method as in Example 24 except that (a) the water activity Aw: 0.99. After storage for 2 months, the appearance of the cheese cod was visually observed, and no change in appearance was observed ( Figure 2 (b)).

[0245] Comparative Example 4

[0246] In Comparative Example 2, the storage property was evaluated in the same manner as in Comparative Example 2 except that the article contained in the packaging material was changed to cheese cod. After 2 months of storage, the appearance of the cheese cod was visually observed, and mold growth was found ( Figure 2 (c)).

[0247] Comparative Example 5

[0248] In Comparative Example 3, the storage property was evaluated in the same manner as in Comparative Example 3 except that the article contained in the packaging material was changed to cheese cod. After 2 months of storage, the appearance of the cheese cod was visually observed, and mold growth was found ( Figure 2 (d)).

[0249] Industrial Applicability

[0250] According to the present invention, it is possible to provide an oxygen absorber which is particularly suitable for storing water-containing articles or storing articles in a high-humidity environment, and a method for storing articles using the oxygen absorber.

Claims

1. An oxygen absorbing material, comprising: Base material (I), Inorganic layer (II), and a cured product layer (III) of an epoxy resin composition containing an epoxy resin and an epoxy resin curing agent, wherein the epoxy resin curing agent includes an amine curing agent, The inorganic layer (II) is adjacent to the cured material layer (III).

2. The oxygen absorbing material according to claim 1, wherein The amine curing agent comprises a reaction product of the following components (A) and (B), (A) at least one selected from the group consisting of m-xylylenediamine and p-xylylenediamine (B) at least one selected from the group consisting of an unsaturated carboxylic acid represented by the following general formula (1) and its derivatives In formula (1), R 1 , R 2 Each independently represents a hydrogen atom, an alkyl group having 1 to 8 carbon atoms, an aryl group having 6 to 12 carbon atoms, or an aralkyl group having 7 to 13 carbon atoms.

3. The oxygen absorbing material according to claim 1 or 2, wherein The inorganic layer (II) is an aluminum vapor-deposited layer.

4. The oxygen absorber according to any one of claims 1 to 3, wherein The substrate (I) is a plastic film.

5. The oxygen absorber according to any one of claims 1 to 4, wherein The oxygen absorber comprises a substrate (IA), the inorganic layer (II), the cured product layer (III), and a substrate (IB) in this order.

6. The oxygen absorbing material according to claim 5, wherein The substrate (IA) and the substrate (IB) are substrates formed of the same resin.

7. The oxygen absorbing material according to claim 6, wherein The substrate (IA) and the substrate (IB) are polypropylene films.

8. The oxygen absorber according to any one of claims 1 to 7, wherein In the epoxy resin composition, the ratio of the number of active hydrogens in the epoxy resin curing agent to the number of epoxy groups in the epoxy resin (the number of active hydrogens in the epoxy resin curing agent / the number of epoxy groups in the epoxy resin) is in the range of 0.2 to 8.

0.

9. A method for storing an article using the oxygen absorbent material according to any one of claims 1 to 8, the method comprising any one or more of the following (1) or (2): (1) placing the article in a packaging material enclosing the oxygen absorbing material; (2) The article is placed in a packaging material, wherein the packaging material has the oxygen absorbing material in at least a portion thereof, and the oxygen permeability of the packaging material is 1 cc / (m 2 ·day·atm) or less.

10. The method according to claim 9, wherein: The relative humidity in the packaging material is above 85%.

11. The method according to claim 9 or 10, wherein: The packaging material containing the articles is stored in an environment with a relative humidity of 85% or more.

12. The method according to any one of claims 9 to 11, wherein: The article contains water.

13. Use of a laminate as an oxygen absorbing material, the laminate comprising: Base material (I), Inorganic layer (II), and a cured product layer (III) of an epoxy resin composition containing an epoxy resin and an epoxy resin curing agent, wherein the epoxy resin curing agent includes an amine curing agent, The inorganic layer (II) is adjacent to the cured material layer (III).

Citation Information

Patent Citations

  • Oxygen-absorbing resin composition

    JP2015007148A

  • Oxygen absorbent

    JP2016140810A

  • Epoxy resin composition, gas barrier film, and laminate

    CN114222796A

  • Gas barrier packaging material

    CN114269815A

  • Amine-based epoxy resin curing agent and epoxy resin composition

    JP2010285537A